Biegefestigkeit von Trägern aus kreissektorförmigen Lamellen - Windeck, Lukas (Karlsruher Berichte zum Ingenieurholzbau, 2022)
Laminated Segment Timber (LST) consists of mutually glued trapezoidal lamellas made of Spruce. Due to the optimization of process parameters the wood yield can be increased to an average of 85 %. LST and layered LST are regulated in ETA-19/0832. Simulation studies deal with the characteristic bending strength at variing member depth and height as well as modifications in the production process.